DIGITAL MEDIA USE OF GENERATION Z DURING COVID-19 PANDEMIC - Fiona Suwana; Alila Pramiyanti; Ira Dwi Mayangsari; Reni Nuraeni; Yasinta Firdaus (Jurnal Sosioteknologi, 2020)
This study examines the depth (frequency), and width (different types) of digital media use about COVID-19 pandemic by Indonesian Gen Z. Participants come from several regions and consist of Gen Z who were born between 1995-2010. A survey towards 326 participants found that WhatsApp, Instagram, and YouTube are platforms that were used by Gen Z in their daily life. Meanwhile, this generation chose WhatsApp as the platform to share information on COVID-19 and other platforms like Instagram and Twitter to receive and post information, image, video, opinion, and personal experiences related to COVID-19. Finding also shows that in daily life, the participants can be categorised as heavy users because they spent more than four hours a day to use digital media. In contrast, they only spent less than an hour per day to find and share information about COVID-19. Therefore, this study argues that there are differences in media preference between daily life and toward COVID-19 pandemic information.